Ending confinement and segregation: barriers to realising human rights in the everyday lives of people living with dementia in residential aged care. Issue 2 (3rd May 2020) - Steele, Linda; Swaffer, Kate; Carr, Ray; Phillipson, Lyn; Fleming, Richard
ABSTRACT: Human rights are increasingly being considered in Australian law reform and policy discussions on how to improve the circumstances of people living with dementia in care homes. This article enriches understanding of the views on human rights held by people living with dementia and those who support, advocate and care for them, in order to ensure that law and policy reforms that promote human rights can be meaningfully enjoyed in practice. Drawing on data from focus groups and interviews with people living with dementia, care partners, aged care workers, and lawyers and advocates, this article argues that there is general support among stakeholders for human rights. However, this support was qualified by their acknowledgement of entrenched economic, cultural and sociolegal barriers to the recognition of human rights in the everyday lives of people living with dementia. The article concludes that urgent action is required to transform the cultural, economic and social drivers of ambivalence and resistance to dementia and human rights within aged care and the broader community.